PENERAPAN MODUL BAHAN AJAR SPECTRUM ANALYZER TERHADAP HASIL BELAJAR SISWA - Fatmawati Sabur; Mulyadi Nur (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Penerbangan Palembang, 2021)
Learning based on student-centered learning makes students the center of learning, where students are encouraged and allowed to seek information from various learning sources, such as learning modules independently. Therefore, we need teaching material that can be used by students without depending on others in their learning. One of the learning media that can be used by students independently is the use of modules. The purpose of this service activity is to socialize the application of the spectrum analyzer module to support learning activities by applying the problem-based learning method. The method used in this service activity is in the form of socialization to Aviation Vocational School students. The results of the service activities obtained good student response data to the spectrum analyzer module as a learning medium which is expected to improve aircraft learning outcomes.